2019
DOI: 10.1088/1361-6587/ab24ae
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for the importance of multi-scale interactions in turbulent transport simulations

Abstract: Turbulent transport simulations have been used to develop criteria that indicate when multi-scale turbulent phenomena are important in tokamak plasmas. Twelve experimental plasma discharges from the Alcator C-Mod and ASDEX Upgrade tokamaks are compared to ion-and multi-scale simulations with the Trapped Gyro-Landau Fluid (TGLF) turbulence code. Multi-scale TGLF agrees with all available validation constraints (ion heat flux, electron heat flux, electron temperature fluctuations, and electron perturbative therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 44 publications
2
23
3
Order By: Relevance
“…2016, 2017; Creely et al. 2019), though their interpretation differs from that given here: Staebler et al. (2016, 2017) and Creely et al.…”
Section: Discussioncontrasting
confidence: 64%
See 3 more Smart Citations
“…2016, 2017; Creely et al. 2019), though their interpretation differs from that given here: Staebler et al. (2016, 2017) and Creely et al.…”
Section: Discussioncontrasting
confidence: 64%
“…Near-marginal ITG turbulence is dominated by zonal modes, see, e.g. , Dimits et al (2000) and Rogers et al (2000). Zonal modes have a structure that depends only on radial position, and hence the long-wavelength E × B driftv E only has the effect of shifting the ETG fluctuation frequency by a Doppler shift: for zonal modes whereφ =φ(x), the termv E • ∇g in (2.2) can be removed by boosting to a toroidally rotating frame (Hardman 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ion temperature gradient (ITG) modes, with some electron-scale activity in the outer part of the plasma core. Recent work (Howard et al 2016;Creely et al 2019) has suggested that multi-scale effects may play a strong role in the prediction of turbulent transport only if (γ /k) high-k > (γ /k) low-k , which is a condition not met at most radii in SPARC under the modelling assumptions used in this analysis.…”
Section: Transport Physicsmentioning
confidence: 96%